2014
DOI: 10.1186/s13071-014-0513-7
|View full text |Cite
|
Sign up to set email alerts
|

A city park as a potential epidemic site of scrub typhus: a case–control study of an outbreak in Guangzhou, China

Abstract: BackgroundScrub typhus is an important public health problem in China, especially in Guangzhou city. Typical outbreaks of scrub typhus have been previously reported in rural areas, affecting mainly farmers. We describe an atypical outbreak of the disease with case fatalities, from a park in Haizhu District, Guangzhou, that could turn out to be a potential scrub typhus epidemic site.MethodsFrom May 2012 to June 2012, a case–control study was conducted to identify source and risk factors of this outbreak. Report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 24 publications
(30 reference statements)
1
19
0
Order By: Relevance
“…Previous studies conducted in Taiwan and rodents at home has also been found to be a significant factor associated with the risk of ST in Luhe. Thus, findings similar to this study was reported in Darjeeling city, which is located in northeast India, but not so in Beijing, China [9,[17][18]. The data subjected to multivariate logistic regression specified that those having a morning exercise in the park and those working in the vegetable field were significantly associated with the occurrence of scrub typhus.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies conducted in Taiwan and rodents at home has also been found to be a significant factor associated with the risk of ST in Luhe. Thus, findings similar to this study was reported in Darjeeling city, which is located in northeast India, but not so in Beijing, China [9,[17][18]. The data subjected to multivariate logistic regression specified that those having a morning exercise in the park and those working in the vegetable field were significantly associated with the occurrence of scrub typhus.…”
Section: Discussionsupporting
confidence: 85%
“…The geographic distribution of scrub typhus depends on the population density and vector competence of local chigger vectors [6]. Statistical studies aimed at predicting and preventing the occurrence of scrub typhus infections have been con-ducted both inside and outside Korea with respect to human outdoor activities and to the time spent on activities such as preventive measures as well as the duration of exposure in chigger habitats such as grasses [8,9]. A statistical model was recently presented for scrub typhus occurrence and included climatic factors such as precipitation and humidity, and the occurrence of scrub typhus cases [9].…”
Section: Introductionmentioning
confidence: 99%
“…Patients that have been bitten by an infected vector typically develop general flu-like symptoms within 1-2 weeks, including fever, headache, coughing, and muscle pain, and they often also present lymphadenopathy, nausea, vomiting, or abdominal pain (Warrell et al 2003;Mahajan 2005;Jeong et al 2007). However, in severe cases, symptoms can include jaundice, acute renal failure, acute respiratory distress syndrome, myocarditis, meningitis, intravascular complications, severe pneumonitis, peritonitis, and cardiac distress, and can even result in death (Peter et al 2015;Biggs et al 2016;Mahajan et al 2008;Tshokey et al 2017;Wei et al 2014;Takhar et al 2017). In the preantibiotic era, the fatality rate was approximately 35-50% (Smadel & Elisberg 1965;Kawamura & Tanaka 1988;Taylor et al 2015).…”
Section: Introductionmentioning
confidence: 99%